Changing sidestep cutting technique reduces knee valgus loading - Dempsey, A. R.; Lloyd, D. G.; Elliott, B. C.; Steele, J. R.; Munro, B. J. (The American Journal of Sports Medicine, 2009)
Common lower limb postures have been found when noncontact anterior cruciate ligament (ACL) injuries occur during sidestep cutting tasks. These same postures have been linked to knee loadings known to stress the ACL.